Answer:
The extraneous solution to the logarithmic equation is
![x=-4](https://img.qammunity.org/2020/formulas/mathematics/college/wvzyemwe3v3nwgy07u4gzjvgd9ub6bpwgv.png)
Explanation:
We have the equation:
![Log_(7) (3x^3+x)-Log_7(x)=2](https://img.qammunity.org/2020/formulas/mathematics/college/36gu58cuy050b7c308frn94qtt0wvdh8aq.png)
By properties of logarithms:
![LogA-LogB=Log((A)/(B))](https://img.qammunity.org/2020/formulas/mathematics/college/8mxs6996sd917l0tkdrtludaodku1e0p5t.png)
So, with the equation we have:
![Log_(7) ((3x^3+x))/(x)=2](https://img.qammunity.org/2020/formulas/mathematics/college/vb94mkaxv06qt4hjmpd03rg10la8e86i3r.png)
![Log_(7)( (3x^3+x)/(x))=2\\Log_(7)( (3x^3)/(x)+(x)/(x))=2\\Log_(7)( (3x^3)/(x)+1)=2\\Log_(7)(3x^2+1)=2](https://img.qammunity.org/2020/formulas/mathematics/college/s4xcchiajrv2gpp3qe2odff1hbukfxs1rs.png)
This logarithm base is 7 and this equation is equal to 2, the number 7 passes as the base on the other side of the equation and the two as an exponent, after that we just to find x:
![7^2=(3x^2+1)\\49=3x^2+1\\49-1=3x^2\\(48)/(3) =x^2\\16=x^2](https://img.qammunity.org/2020/formulas/mathematics/college/5588cwxd7utcu3rdi0otiu1tcbzcxxtha5.png)
Now, we can find x with square root
![16=x^2\\√(16) =√(x^2) \\x_1=4\\x_2=-4](https://img.qammunity.org/2020/formulas/mathematics/college/ouhf4iyww2ar99wc7zqem489y5mceclc2q.png)
This equation has two answers because it is a quadratic equation, so with this logic the strange solution is -4